(untitled) (Muitas Vozes, 2021)
This article aims to analyze the critical reception of the novel A maçã no escuro, by Clarice Lispector (1920-1977), configuring itself in two distinct and particular readings of the narrative, developed by the critic and philosopher Benedito Nunes, in O Drama da linguagem (1995) , and by critic Evandro Nascimento, in Clarice Lispector: uma literatura pensante (2012). Thus, we will approach two themes that are the key to the readings. It is the dramatic of the language and mystical pilgrimage in Nunes, and the wild calling and vocation in Nascimento. In the interpretive work of those critics, we will verify how the authors direct their readings, raising questions and problems regarding the conjuncture of the work, in its aesthetic and thematic realization.